Strategies of quantity surveying firms to reduce turnover intention - Tan, Chin Keng; Mohamed Nor, Nik Nur Azirah; Yeoh, Kah Ching (Science Publishing Corporation, 2019)
Quantity Surveyors are among the key players involved in a construction project. A Quantity Surveyor involves in the financial and contractual matters starting from the initiation stage until to the completion of handling a construction. Thus, a Quantity Surveyor is the key player who has the responsibility in handling financial, contract management and others. This study is concerned on the issue of job satisfaction and turnover intention among Quantity Surveyors. The objective of this research is to explore strategies of Quantity Surveying firms in Malaysia to increase job satisfaction and reduce turnover intention among their technical employees. The interview is the methods used to collect data for this study. The interview was conducted with five (5) technical employees and five (5) employees from Human Resources department of Quantity Surveying firms. The respondents are technical employees and employees from Human Resources department of any Quantity Surveying firms in Kuala Lumpur. The findings conclude that the items of strategy suggested to reduce turnover intention by increasing job satisfaction can be grouped according to the constructs of opportunities and rewards, nature of work, working relationship with immediate superior, organizational factors and social interaction.